PENERAPAN STRATEGI LEARNING CYCLE UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTsN BATANG KAPAS TAHUN AJARAN 2012/2013 - Meli, Refsi; Nasution, Minora Longgom; Aima, Zulfitri (STKIP PGRI Sumbar, 2013)
The low students achievement in mathematics learning on MTsN Batang Kapas will become the background in this research. So, the purpose of the research is to find out whether does comprehension of mathematical concepts of students by using strategy learning cycle give significant effect better than mathematical concepts of students by using conventional study. The design of this research is experimental research. The population in this research is all of students at eight grade MTsN Batang Kapas in 2012/2013 academic years. Researcher thought the way of choosing sample by using random sampling, which is the sample of class VIIIA and VIIIB. In this case, the instrument that the researcher will use is comprehension of mathematical concepts. The form of this test is essay,Â which is the reliability of this test is r11=0,85. Technique of data analysis will use ttest. Based on the hypothesis testing, P-value=0,035 < Î±=0,05. So, this hypothesis is accepted. It means comprehension of mathematical concepts of students by using the strategy learning cycle better than comprehension of mathematical concept of students by using conventional study.